2003
DOI: 10.1128/mcb.23.21.7719-7731.2003
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylation of RB-Responsive Promoters: Requisite for Specific Gene Repression but Dispensable for Cell Cycle Inhibition

Abstract: The retinoblastoma tumor suppressor protein (RB) is targeted for inactivation in the majority of human tumors, underscoring its critical role in attenuating cellular proliferation. RB inhibits proliferation by repressing the transcription of genes that are essential for cell cycle progression. To repress transcription, RB assembles multiprotein complexes containing chromatin-modifying enzymes, including histone deacetylases (HDACs). However, the extent to which HDACs participate in transcriptional repression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 78 publications
(95 reference statements)
3
84
0
Order By: Relevance
“…Chromatin acetylation is known to result in its decondensation, thus facilitating access of transcription machinery to the promoter regions of tumor suppressor genes. 27 Chromatin immunoprecipitation results (Figure 7b) demonstrated that depending on the stress level, DNA damaging drugs can induce histone acetylation and induction of the tumor suppressor p21/WAF1 without significant induction of DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin acetylation is known to result in its decondensation, thus facilitating access of transcription machinery to the promoter regions of tumor suppressor genes. 27 Chromatin immunoprecipitation results (Figure 7b) demonstrated that depending on the stress level, DNA damaging drugs can induce histone acetylation and induction of the tumor suppressor p21/WAF1 without significant induction of DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…It cannot be ruled out that the observed changes could be a parallel issue as for example growth inhibition, induced by sodium butyrate, has been described in a cell line that has abrogated Rb function (Rashid et al, 2001). There might be other and potentially even more important structures such as cyclin A and D, p27 and protein kinase C, which are involved in the process of butyrate-induced growth inhibition (Chen et al, 2003;Kim et al, 2003;Siddiqui et al, 2003). Nevertheless, exploring the activation of p-21, including the role of Sp1 transcription factor, is a very promising approach (Wang et al, 2000;Rashid et al, 2001;Margueron et al, 2003), as this gene appears to be rarely mutated in common human malignancies in contrast to p53 (Terao et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…HDACi should therefore lead to activation of RB targets, effectively enhancing a key proliferative pathway. Despite these reservations, HDAC recruitment seems crucial only for a subset of RB targets, and cell-cycle regulation by RB proceeds largely through HDACindependent mechanisms 80 .…”
Section: The Cellular Effects Of Hdacimentioning
confidence: 99%